Strategi Pemasaran Mengenai Persepsi Harga, Kualitas Produk, dan Kepuasan Konsumen Terhadap Keputusan Pembelian Perumahan Gempol Citra Asri - Hermawan, Diky; Indayani, Lilik; Sudarso, Satrio (Universitas Batanghari, 2024)
This research aims to analyze marketing strategies regarding price perceptions, product quality and consumer satisfaction regarding purchasing decisions for Gempol Citra Asri housing. This research was conducted at the Gempol Citra Asri Housing Complex. This research uses quantitative methods. The sample used in this article used the Slovin Formula and found 115 respondents. The sampling technique uses non-probability with the accidental sampling method, where the researcher selects samples and takes respondents who are available at the research site. The results obtained in this research indicate that price perception has a positive and significant influence on purchasing decisions for Gempol Citra Asri Housing, product quality has a positive and significant influence on purchasing decisions for Gempol Citra Asri Housing, and consumer satisfaction has a positive and significant influence on purchasing decisions for Gempol Citra Asri Housing. And it can be concluded that price perception, product quality and consumer satisfaction have a positive and significant influence on purchasing decisions for Gempol Citra Asri housing.